2013
DOI: 10.2337/dc12-1925
|View full text |Cite
|
Sign up to set email alerts
|

Exenatide-Induced Reduction in Energy Intake Is Associated With Increase in Hypothalamic Connectivity

Abstract: OBJECTIVEGlucagon-like peptide-1 receptor agonists such as exenatide are known to influence neural activity in the hypothalamus of animals and to reduce energy intake. In humans, however, significant weight loss has been observed in only a subgroup of patients. Why only some individuals respond with weight loss and others do not remains unclear. In this functional magnetic resonance imaging (fMRI) study, we investigated differences in hypothalamic connectivity between “responders” (reduction in energy intake a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 37 publications
1
46
0
Order By: Relevance
“…Lower scores indicate that hunger feelings (which are often perceived as disturbing) are decreased (18). Of note in this context is that another physiological anorexigenic peptide hormone, the GLP-1 agonist exenatide, had similar effects on the hypothalamus in fMRI connectivity analysis as well as on VAS-assessed hunger and satiety in obese subjects in another study from our group (27). These results combined support the hypothesis that leptin substitution improves homeostatic satiety signaling through the hypothalamus.…”
Section: Discussionsupporting
confidence: 71%
“…Lower scores indicate that hunger feelings (which are often perceived as disturbing) are decreased (18). Of note in this context is that another physiological anorexigenic peptide hormone, the GLP-1 agonist exenatide, had similar effects on the hypothalamus in fMRI connectivity analysis as well as on VAS-assessed hunger and satiety in obese subjects in another study from our group (27). These results combined support the hypothesis that leptin substitution improves homeostatic satiety signaling through the hypothalamus.…”
Section: Discussionsupporting
confidence: 71%
“…Liraglutide effectively lowers body weight in nonobese and obese rats, obese pigs, and humans, and exendin-4 has been show to rapidly circumvent hypothalamic inflammation, all together indicating that nonobese rodents may be a suitable model to describe access to key appetite-regulating neurons (74,79,(84)(85)(86)(87). Also, a clinical study reported an increased hypothalamic connectivity using functional magnetic resonance imaging following a peripheral dose of exenatide (88). The use of neuronal lesion and ablation models has certain limitations, as they interrupt neuronal networks and can potentially induce compensatory responses or affect neuronal functions in distant connected areas.…”
Section: Surgery Models and Compound Administrationmentioning
confidence: 99%
“…Exenatide readily crosses the blood-brain barrier, even more efficiently than native GLP-1 (Kastin & Akerstrom 2003), and it has been shown to activate brain regions involved in food reward and glucose homeostasis when administered subcutaneously (Daniele et al 2015). The effects of exenatide on food intake may be mediated by its central action, as exenatide-induced reductions in energy intake in humans have been associated with increased hypothalamic connectivity (Schlogl et al 2013), and intracerebroventricular injection of the GLP-1R antagonist, exendin-9, blocks the inhibitory effects of exenatide on energy intake in rodents (Kanoski et al 2011). However, the effects of exenatide on glucose regulation do not appear to be dependent on central GLP-1R activation (Lamont et al 2012), and evidence suggests that exenatide may exert its effects on glycaemia through direct action on the pancreas (Smith et al 2014).…”
Section: Glp-1r Agonistsmentioning
confidence: 99%